Tele-Traffic Simulation for Mobile Communication Systems Beyond 3G - Juarez Valero, Jesus M. (2006)
European projects like Simulation of Enhanced UMTS Access and Core Network (IST-SEACORN) proposed a set of enhancements to UMTS. By considering the deployment scenarios and tele-traffic parameters from the Vehicular scenario of SEACORN, a simulator was produced to extract conclusions about blocking and handover failure probabilities. Simulation, which consider the burstiness of traffic, were performed for different cases, from single- to multi-service situations, and from absence to presence of mobility. Besides quality of service results in the air interface, including blocking and handover failure probabilities, the simulator allows for extracting conclusions about the validation of the Bernoulli/ Poisson/Pascal model for the computation of the ONOFF blocking probability, the ratio between the number of call rejected at the beginning of an ON period and the total number of bursts generated during a session. As the theoretical and the simulation results agree, the validation was achieved.